Growth performance and immune response of broilers during active Eimeria infection are modified by dietary inclusion of canola meal or corn-DDGS in reduced-protein corn-soybean meal diets - Revathi Shanmugasundaram; Adeleye M. Ajao; Shahna Fathima; Adelumola Oladeinde; Ramesh K. Selvaraj; Todd J. Applegate; Oluyinka A. Olukosi (Animal Nutrition)
The objective of this experiment was to study the effects of partial replacement of soybean meal (SBM) with canola meal (CM) or corn-distillers' dried grains with solubles (cDDGS) in reduced-protein (RP) diets for Eimeria-infected broilers. A total of 1120 broiler chicks were distributed in a 4 × 2 (4 diets × with or without infection) factorial arrangement with 7 replicates per treatment and 20 birds per replicate. The 4 diets, fed between d 7 and 42, were (i) a standard diet with crude protein at 200 g/kg (SP); (ii) a RP (crude protein at 160 g/kg) corn-SBM diet (RP-SBM); (iii) a RP diet in which 80 g/kg CM replaced 60 g/kg SBM (RP-CM); and (iv) a RP diet in which 100 g/kg cDDGS replaced 50 g/kg SBM (RP-cDDGS). On d 15, birds were infected with mixed Eimeria (+E) oocysts. Birds and feed were weighed at intervals for growth performance, and samples for immunology responses were collected on d 21. The results showed as follows: 1) during the acute infection phase, diet × Eimeria infection was shown by the diets having no effect in the uninfected group. In contrast, the RP-SBM diet tended to produce higher (P < 0.10) weight gain among the infected birds. The d 42 body weight was greater (P = 0.001) for the uninfected birds. 2) There was a significant diet × Eimeria infection on bile anti-Eimeria immunoglobulin A (IgA) concentrations (P = 0.015), splenocyte proliferation, macrophage nitric oxide (NO) production (P < 0.001), and cecal tonsil interleukin (IL)-17 mRNA amounts (P < 0.001). Most of these responses were not influenced by the diets in the uninfected birds. However, among the infected birds, birds fed RP-SBM had higher (P < 0.05) bile IgA than those fed SP or RP-cDDGS. For the spleen, the interaction was that birds fed RP-SBM or RP-cDDGS diets had the highest or lowest NO production, respectively, and birds that received RP-SBM had greater (P < 0.05) splenic CD8+:CD4+ cell ratio than other diets. In conclusion, partial replacement of SBM with CM or cDDGS had only a marginal effect on d 42 body weight and FCR of the broiler chickens receiving the RP diets. In contrast, these had a negative impact on the immune responses of the broiler chickens.